Usłyszane dziedzictwo. Szkic z dźwiękowej etnografii .......... 73 - Sochacki, Łukasz (Niematerialne dziedzictwo kulturowe w teorii i praktyce, 2021)
A SKETCH IN SOUND ETHNOGRAPHYThe article considers the idea of the soundscape as intangible cultural heritage. Theoretical considerations were supplemented and confronted with empirical materials collected during ethnographic field research. The soundscape surrounding sheep shepherds in the Poprad Valley was selected for the case study. The author argues that ordinary sounds of everyday life are overlooked as an element of intangible cultural heritage. However, based on the fragment of ethnographic material presented in the article, he attempts to show that the soundscape of everyday life is an important element of intangible cultural heritage and may determine its durability.